Seleksi, Karakterisasi, dan Reaktivitas Antibodi Monoklonal Virus Kerdil Kedelai - Sri Sulandari; Y. B. Sumardiyono; Roechan M. (Universitas Gadjah Mada, 2003)
Soybean Stunt Virus (SSV) is a member of Cucumber mosaic virus group that caused soybean stunt disease. The disease is the most important viral disease of soybean in Indonesia. The objective of the study was to obtain SSV monoclonal antibody for detection SSV in both infected seed and plant. Six hybridoma clones were obtained from fusion between spleen cells of BALB/c immunized with Soybean stunt virus and mouse myelome cell lines (NS-1); they were IgG3 type antibodies, and its titres were varied between 1: 1O to 1: 1OO. Using non-recoated I-ELISA method, the homolog antigen (SSV) was well detected but not the heterolog antigens (CMV isolated from banana, tobacco).